Optimization of VAM as Pattern – Connected Edge Weighed Graph - et. al., K. Thiagarajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this approach is to find the optimal cost of the transportation grid in Balanced and unbalanced ways of the TPM derived from the edge weighted connected non-complete graph. The proposed approach of this article is in a particular path representation of the given transportation problem to ensure the Optimal Basic Feasible Solution by Vogel’s Approximation Method for the derived TPM from the edge weighted connected non-complete graph. Optimal Basic Feasible Solution is also provided with the existed methods in operation research field with particular pattern at some extent